New material for tetracycline colorimetric detection and preparation method and application thereof

By developing a colorimetric detection method based on MnO2@ZIF-67@MAA composite material, the complex and expensive problems of existing tetracycline detection methods are solved, and the rapid, sensitive and selective detection of tetracycline is achieved, which is suitable for the detection of medical wastewater and milk.

CN119757327APending Publication Date: 2025-04-04HEBEI UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411727482.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing tetracycline detection methods have complex preprocessing procedures, long analysis cycles, expensive equipment and well-trained personnel needs, and the fluorescence analysis method uses toxic compounds, and electrochemical analysis method is cumbersome.

Method used

A colorimetric detection method based on MnO2@ZIF-67@MAA composite material is developed. This method achieves rapid, sensitive and selective detection of tetracycline through the enhanced peroxidase-like activity of MnO2@ZIF-67@MAA, combining the reaction of H2O2 and chromogenic substrate.

Benefits of technology

The rapid, sensitive and selective detection of tetracycline is achieved, with a detection limit of 0.025μM. It is suitable for tetracycline detection in medical wastewater and milk. The reaction conditions are mild and the operation is simple.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005159544560000081
    Figure BDA0005159544560000081
  • Figure HDA0005159544580000011
    Figure HDA0005159544580000011
  • Figure HDA0005159544580000012
    Figure HDA0005159544580000012
Patent Text Reader

Abstract

The invention provides a novel material for tetracycline colorimetric detection and a preparation method and application thereof. The composite material MnO2 (at) ZIF-67 (at) MAA based on the MnO2 (at) ZIF-67 (at) coated with the MAA polymer layer is synthesized, and the composite material has good thermal stability and peroxidase-like performance. When a solution contains tetracycline (TC), the TC interacts with MnO2 (at) ZIF-67 (at) MAA through interaction of a pi-pi bond and multiple hydrogen bonds, so that the capacity of the MnO2 (at) ZIF-67 (at) MAA for catalyzing H2O2 to oxidize TMB is enhanced, the intensity of generated blue is promoted, and a TC detection platform is established. The TC can be detected through colorimetric detection or absorbance detection, the cost is low, the selectivity is good, the method is not influenced by other components in a sample to be detected, a new thought is provided for efficient and accurate detection of TC in medical wastewater and milk, and the method has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tetracycline detection, in particular to a new material for tetracycline colorimetric detection and a preparation method and application thereof. Background Art

[0002] Tetracycline (TC), as an antibacterial, highly effective and low-cost veterinary antibiotic, is widely used in the prevention, control and treatment of animal diseases. However, the misuse and overuse of TC have led to antibiotic resistance and antibiotic disasters. Stubborn TC molecules are difficult to be fully digested and metabolized in animals, resulting in more than 70% of TC residues being released into the environment through urine and feces, seriously threatening the balance of the ecosystem. In addition, when humans consume foods with excessive TC, it can cause allergic reactions, bone dysplasia, liver damage, gastrointestinal disorders and bacterial resistance. To ensure food safety, the World Health Organization stipulates that the maximum residue limit of TC in animal-derived foods is 100 μg kg -1 Therefore, prioritizing the control and monitoring of TC in the environment and in foods of animal origin is of great significance for improving food safety and protecting human health.

[0003] So far, researchers have explored a variety of analytical methods for detecting TC, such as high performance liquid chromatography, liquid chromatography-mass spectrometry, capillary electrophoresis, chromatoimmunoassay, electrochemical analysis, fluorescence analysis, colorimetric analysis, etc. However, chromatography requires complex pretreatment procedures, long analysis cycles, expensive instrumentation, and well-trained personnel, fluorescence analysis sometimes requires the use of some toxic organic compounds as a fluorescence source, and electrochemical analysis requires cumbersome electrode processing procedures. These factors have seriously hindered their use in practical applications. Among them, the advantages of colorimetric sensing are multifaceted, including portability, simplicity, rapid analysis, and visual readability, and it has attracted considerable attention as a means of on-site screening analysis.

[0004] Nanozymes are nanomaterials with natural enzyme-like activity. They have been rapidly developed in recent years due to their low cost, good catalytic stability, flexible structural design, and easy functionalization. In sensing applications, nanozymes amplify reaction signals through their catalytic properties, thereby achieving the effect of improving sensor sensitivity. Therefore, it is of great significance to develop a new detection technology that combines the catalytic properties of nanozymes with colorimetric sensing methods. Summary of the invention

[0005] The purpose of the present invention is to provide a new material for colorimetric detection of tetracycline and its preparation method and application. Specifically, the material used for detecting tetracycline in the present invention is a new composite material MnO 2@ZIF-67@MAA, the colorimetric detection method of tetracycline based on this new composite material, has the advantages of rapidity, sensitivity and good selectivity, which provides a new idea for the efficient and accurate detection of tetracycline in medical wastewater and milk, and has broad application prospects.

[0006] The present invention is achieved in that:

[0007] A new material for colorimetric detection of tetracycline, which is composed of methacrylic acid encapsulating MnO 2 @ZIF-67 nanocomposite material MnO 2 @ZIF-67@MAA.

[0008] The preparation method of the new material for tetracycline colorimetric detection comprises the following steps:

[0009] S1. Preparation of MnO 2 Nanosheets: Tetramethylammonium hydroxide aqueous solution, H 2 O 2 The solution was mixed with an aqueous solution of manganese chloride, and after magnetic stirring, the precipitate was washed several times with water and methanol, and then dried to obtain MnO 2 Nanosheets;

[0010] S2. Preparation of MnO 2 @ZIF-67: Cobalt nitrate methanol solution and MnO 2 The nanosheets were mixed and magnetically stirred; then a methanol solution of 2-methylimidazole was added and magnetically stirred; after standing, the supernatant was discarded, centrifuged, and the precipitate was washed several times with methanol and then dried to obtain MnO 2 @ZIF-67;

[0011] S3. Preparation of MnO 2 @ZIF-67@MAA composite material: methacrylic acid, MnO 2 @ZIF-67 is added to ethylene glycol dimethacrylate, and then azobisisobutyronitrile is added to the mixture. 2 After the reaction is completed, the obtained solid is washed with methanol until it is neutral, and then dried to obtain the composite material MnO 2 @ZIF-67@MAA.

[0012] The composite material MnO prepared by the method of the present invention 2 @ZIF-67@MAA can be used in the colorimetric detection of tetracycline. The specific detection method is as follows:

[0013] (1) Preparation of tetracycline standard solution: Weigh tetracycline powder and dissolve it in ultrapure water, and prepare tetracycline standard solutions of different concentrations by dilution;

[0014] (2) Preparation of incubation system: MnO 2 @ZIF-67@MAA was mixed with acetate buffer, and then the tetracycline standard solution of different concentrations prepared in step (1) was added;

[0015] (3) Preparation of reaction system: Add H 2 O 2 The solution and the color developing substrate 3,3',5,5'-tetramethylbenzidine solution were incubated for reaction;

[0016] (4) Detection: Determine the ultraviolet absorbance A of the reaction system obtained in step (3) at a wavelength of 650 nm; Determine the absorbance A of the reaction system at a wavelength of 650 nm when there is no target tetracycline 0 ; Then, the concentration of tetracycline was used as the horizontal axis, and the measured A and A 0 The absorbance difference ΔA was used as the ordinate to obtain the linear relationship between the tetracycline concentration and the absorbance difference ΔA;

[0017] (5) MnO 2 @ZIF-67@MAA was mixed with acetate buffer, and then the sample to be tested was added; after the reaction, H 2 O 2 The solution and the color developing substrate 3,3',5,5'-tetramethylbenzidine solution were incubated for reaction;

[0018] (6) Detecting the ultraviolet absorbance of the reaction system at a wavelength of 650 nm in step (5), and calculating the relationship between the ultraviolet absorbance and A 0 The difference between

[0019] (7) Based on the UV absorbance and A obtained in step (6) 0 The difference between the values ​​of , combined with the linear relationship obtained in step (4), is used to calculate the concentration of tetracycline in the sample to be tested.

[0020] In the above scheme, preferably, the tetracycline standard solutions of different concentrations in step (1) refer to tetracycline concentrations of 1, 2, 5, 10, 50, 100, and 200 μM, respectively.

[0021] In the above scheme, preferably, in step (2), MnO 2 The concentration of @ZIF-67@MAA was 0.67 mg mL -1 ; After adding tetracycline, react at room temperature for 90 minutes.

[0022] In the above scheme, preferably, in step (3), H 2 O 2The concentration of the solution was 0.02 M, the concentration of the 3,3',5,5'-tetramethylbenzidine solution was 0.24 mM, and the incubation reaction was carried out at room temperature for 10 minutes.

[0023] In the above scheme, preferably, in step (4), the absorbance A of the reaction system at a wavelength of 650 nm is measured when there is no target tetracycline. 0 , means that in step (2), no tetracycline standard solution is added, and then the ultraviolet absorbance of the reaction system obtained in step (2) and step (3) is measured at a wavelength of 650 nm, which is recorded as A 0 .

[0024] In the above scheme, preferably, in step (4), the ultraviolet absorbance of the system is measured at a wavelength of 650nm, specifically: the sample is placed in a UV-visible spectrophotometer and a full wavelength scan of 200 to 800nm ​​is performed to determine the absorbance value at 650nm.

[0025] In the above scheme, preferably, the sample to be tested in step (5) is medical waste water or milk.

[0026] The specific technical effects of the present invention are as follows:

[0027] 1. The present invention creatively uses MnO with peroxidase-like activity 2 @ZIF-67@MAA composite material is used as the detection platform. When TC is added, MnO 2 The enzyme-like activity of @ZIF-67@MAA was significantly enhanced. As the concentration of TC increased, the blue intensity of the system gradually increased. At the same time, the absorbance at 650nm increased. 2 @ZIF-67@MAA was used as a colorimetric sensing material to accurately determine the content of TC in samples.

[0028] 2. Add different concentrations of TC to the MnO 2 When @ZIF-67@MAA was added to the acetate buffer solution, the absorbance A at 650 nm gradually increased with the increase of TC concentration. The results showed that the absorbance difference ΔA between the reaction system and the blank group showed a good linear relationship with TC in the concentration range of 0.1-20 μM, and the detection limit reached 0.025 μM.

[0029] 3. The reaction conditions of the present invention are mild, the detection process is easy to operate, the response speed is fast, and strict time control is not required.

[0030] 4. The method of the present invention was successfully applied to the detection of TC in medical wastewater and fresh milk samples. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1The MnO prepared in Examples 1 and 2 of the present invention 2 @ZIF-67 @MAA and MnO 2 @UV-visible absorption spectra of ZIF-67 composite materials under different catalytic systems (the inset shows the color changes of the corresponding systems).

[0032] Figure 2 MnO in Example 4 of the present invention 2 UV-visible absorption spectra of @ZIF-67@MAA composites in response to TC solutions of different concentrations.

[0033] Figure 3 MnO in Example 5 of the present invention 2 ΔA-TC concentration curve of @ZIF-67@MAA composite material in response to TC solutions of different concentrations.

[0034] Figure 4 MnO in Example 6 of the present invention 2 Storage stability analysis results of @ZIF-67@MAA composites.

[0035] Figure 5 MnO in Example 7 of the present invention 2 Absorbance values ​​of @ZIF-67@MAA composite materials in the presence of TC / other interferents system. DETAILED DESCRIPTION

[0036] The present invention provides a novel nanocomposite material MnO 2 @ZIF-67@MAA, nanocomposite MnO 2 @ZIF-67@MAA is a methacrylic acid (MAA) based polymer layer encapsulating MnO 2 @ZIF-67, the material has good thermal stability and peroxidase-like properties. Based on this new nanocomposite material MnO 2 When @ZIF-67@MAA detects tetracycline, when the solution contains tetracycline (TC), TC interacts with MnO through π-π bonds and multiple hydrogen bonds. 2 @ZIF-67@MAA interacts with MnO 2 @ZIF-67@MAA catalyzes hydrogen peroxide (H 2 O 2 )'s ability to oxidize 3,3',5,5'-tetramethylbenzidine (TMB) is enhanced, the intensity of the blue color produced is promoted, and the TC concentration information of the test solution can be obtained by detecting the absorbance value.

[0037] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0038] The acetate buffer, H 2 O 2 Solution, TMB solution and TC solution were prepared as follows:

[0039] 1. Preparation of acetate buffer (NaAc-HAc buffer solution): Use an analytical balance to weigh 1.02 g of crystalline sodium acetate solid, add it to a small amount of ultrapure water to dissolve, transfer it to a 50 mL volumetric flask, then measure 4 mL of analytical glacial acetic acid and transfer it to a 50 mL volumetric flask, add ultrapure water to the mark to obtain the required NaAc-HAc buffer solution.

[0040] 2.0.2M H 2 O 2 Solution preparation: Take 2 mL of 30% H 2 O 2 Place in a 100 mL volumetric flask and add ultrapure water to the mark to obtain 0.2 M H 2 O 2 Solution. Dilute to other concentrations of H 2 O 2 Solution.

[0041] 3. Preparation of 10 mM TMB solution: Weigh 0.0313 g TMB powder solid using an analytical balance and add it to a small amount of dimethyl sulfoxide (DMSO) to dissolve, transfer to a 10 mL volumetric flask, add DMSO to the mark to obtain a 10 mM TMB solution. Dilute to other TMB solutions of different concentrations as needed.

[0042] Preparation of 1mM TC solution: Weigh 24mg TC powder solid using an analytical balance and add it to a small amount of ultrapure water to dissolve, transfer it into a 50mL volumetric flask, add ultrapure water to the mark to obtain a 1mM TC solution. Dilute to other TC solutions of different concentrations as needed.

[0043] Other reagents and materials used in the examples can be obtained through commercial channels.

[0044] Example 1

[0045] Preparation of MnO 2 @ZIF-67@MAA nanocomposite material, the specific steps are as follows:

[0046] 1.MnO 2 Preparation of nanosheets: Tetramethylammonium hydroxide (TMA·OH) (0.7249 g) was dispersed in 200 mL of pure water to obtain a 20 mM TMA·OH solution, which was solution A. 30% H 2 O 2(2 mL) was mixed with 18 mL of pure water to obtain 3.0 wt% H 2 O 2 The solution is solution B. 2 ·4H 2 O (5.9373 g) was dispersed in 100 mL of pure water to obtain 0.3 M MnCl 2 The solution is solution C. Solutions A, B and C were mixed together and stirred magnetically at 25°C and 600 r / min for 12 h. After stirring, the obtained precipitate was washed with water and methanol several times and dried at 60°C to obtain MnO 2 Nanosheets.

[0047] 2. MnO 2 Preparation of ZIF-67: Co(NO 3 ) 2 6H 2 O (0.84 mmol) was dispersed in 50 mL of methanol, and 0.5 g of the above synthesized MnO was added. 2 Nanosheets, 25℃ 600r / min magnetic stirring for 1h. 2-Methylimidazole (66mmol) was dispersed in 50mL methanol to obtain solution A. Then, solution A was added thereto and stirred for 2h. After standing for 1h, the supernatant was discarded and centrifuged. The precipitate was washed with methanol 3 times and dried at 60℃ to obtain MnO 2 @ZIF-67.

[0048] 3.MnO 2 Preparation of @ZIF-67@MAA: MAA (0.2 mmol) was dispersed in 15 mL of dimethyl sulfoxide (DMSO) and mechanically stirred at 25 °C for 1 h. 100 mg of MnO was added to the above solution. 2 @ZIF-67, mechanically stirred at 25 °C for 3 h. 2 After stirring for 20 min, ethylene glycol dimethacrylate (EGDMA) (2 mmol) was added to fix the pre-assembled mixture, the temperature was raised to 60 °C, stirring was continued for 20 min, azobisisobutyronitrile (AIBN) (60 mg) was added, and the mixture was heated at 60 °C. 2 The reaction was carried out under the atmosphere for 12 hours. After the reaction was completed, the solid obtained was washed with methanol until it was neutral and dried at 60°C. The obtained composite material was MnO 2 @ZIF-67@MAA.

[0049] Example 2

[0050] Preparation of MnO 2 @ZIF-67 nanocomposite material, the specific steps are as follows:

[0051] 1.MnO 2 Preparation of nanosheets: TMA·OH (0.7249 g) was dispersed in 200 mL of pure water to obtain a 20 mM TMA·OH solution, which was solution A. 30% H 2 O 2 (2 mL) was mixed with 18 mL of pure water to obtain 3.0 wt% H 2 O 2 The solution is solution B. 2 ·4H 2 O (5.9373 g) was dispersed in 100 mL of pure water to obtain 0.3 M MnCl 2 The solution is solution C. Solutions A, B and C were mixed together and stirred magnetically at 25°C and 600 r / min for 12 h. After stirring, the obtained precipitate was washed with water and methanol several times and dried at 60°C to obtain MnO 2 Nanosheets.

[0052] 2. MnO 2 Preparation of ZIF-67: Co(NO 3 ) 2 6H 2 O (0.84 mmol) was dispersed in 50 mL of methanol, and 0.5 g of the above synthesized MnO was added. 2 Nanosheets, 25℃ 600r / min magnetic stirring for 1h. 2-Methylimidazole (66mmol) was dispersed in 50mL methanol to obtain solution A. Then, solution A was added thereto and stirred for 2h. After standing for 1h, the supernatant was discarded and centrifuged. The precipitate was washed with methanol 3 times and dried at 60℃ to obtain MnO 2 @ZIF-67.

[0053] Example 3

[0054] Test Example 2 obtained MnO 2 @ZIF-67 and MnO obtained in Example 1 2 The enzyme-like activity of @ZIF-67@MAA composites was investigated based on MnO 2 The feasibility of TC colorimetric detection of @ZIF-67@MAA nanocomposites is as follows:

[0055] The specific operation of investigating the oxidase activity is as follows: 2 mg MnO 2 @ZIF-67@MAA, 2.7 mL acetate buffer (pH 3) and 0.3 mL TMB (2.4 mM) solution were mixed, and the mixed system was reacted at room temperature for 10 min. The UV-visible absorption spectrum of the reaction system was recorded in the range of 500-800 nm to obtain MnO 2Oxidase-like activity of @ZIF-67@MAA nanocomposites.

[0056] The specific operation of investigating the peroxidase-like activity is as follows: 2 mg MnO 2 @ZIF-67@MAA, 2.4 mL acetate buffer (pH 3), 0.3 mL H 2 O 2 The (0.2 M) solution and 0.3 mL TMB (2.4 mM) solution were mixed, and the mixed system was reacted at room temperature for 10 min. The UV-visible absorption spectrum of the reaction system was recorded in the range of 500-800 nm to obtain MnO 2 Peroxidase-like activity of @ZIF-67@MAA nanocomposites.

[0057] With the same mass of MnO 2 @ZIF-67 nanomaterials replace MnO 2 @ZIF-67@MAA nanocomposite materials were tested.

[0058] In addition, 2 mg MnO 2 @ZIF-67@MAA, 2.1 mL acetate buffer (pH 3) and 0.3 mL TC (500 μM) were mixed and reacted at room temperature for 90 min, after which 0.3 mL H 2 O 2 (0.2 M) and 0.3 mL TMB (2.4 mM), the mixed system was reacted at room temperature for 10 min and the UV-visible absorption spectrum was recorded in the range of 500-800 nm.

[0059] The above test results can be found in Figure 1 .Depend on Figure 1 It can be seen that [MnO 2 @ZIF-67+TMB] system has no color change and no UV-visible absorption peak at 650nm, while [MnO 2 @ZIF-67+H 2 O 2 +TMB] system has a significant blue color, with obvious UV-visible absorption peak and high absorbance value, indicating that the prepared MnO 2 @ZIF-67 has strong peroxidase-like activity. In addition, MnO 2 @ZIF-67@MAA also exhibited the same peroxidase-like activity. 2 @ZIF-67@MAA+TC+H 2 O 2 +TMB] system has a blue ratio of [MnO 2 @ZIF-67@MAA+H 2 O2 +TMB] is more obvious, and the UV-visible absorption peak is significantly higher, which is the reason for the subsequent MnO 2 @ZIF-67@MAA has laid a solid foundation for the quantitative detection of TC.

[0060] Example 4

[0061] Preparation based on MnO 2 The working curve of TC colorimetric detection method of @ZIF-67@MAA nanocomposite materials, the specific steps are as follows:

[0062] 0.3 mL of TC standard solution of 1, 2, 5, 10, 50, 100, and 200 μM was added to 2 mg of MnO 2 @ZIF-67@MAA was mixed with 2.1 mL acetate buffer (pH 3) and reacted at room temperature for 90 min, after which 0.3 mL H 2 O 2 (0.2 M) and 0.3 mL TMB (2.4 mM) were added to make the final concentration of TC 0.1, 0.2, 0.5, 1, 5, 10, 20 μM. The mixed system was reacted at room temperature for 10 min and the UV-visible absorption spectrum was recorded in the range of 500-800 nm. The results are shown in Figure 2 shown.

[0063] from Figure 2 It can be seen that in MnO 2 In the presence of @ZIF-67@MAA nanocomposites, the absorbance value at 650 nm gradually increased with the increase of TC concentration, and there was a quantitative relationship with the concentration of TC solution.

[0064] Example 5

[0065] The colorimetric detection method of TC was constructed, and the specific steps were as follows:

[0066] By plotting the concentration data of TC and the absorbance difference ΔA obtained during its detection, the working curve of the colorimetric detection method of TC can be obtained. The absorbance difference ΔA refers to the difference in ultraviolet absorbance of the reaction system when TC is present and when TC is not present. Figure 3 As shown in the figure, it can be seen that the ΔA value shows a good linear relationship with the TC concentration, and the linear equation of the working curve is ΔA = 0.0860 + 0.0589c (c = 0.1-20 μM, R 2 =0.9674).

[0067] Example 6

[0068] The present invention provides a method for 2The storage stability of @ZIF-67@MAA nanocomposites was investigated by the following steps:

[0069] 2 mg MnO 2 @ZIF-67@MAA was mixed with 2.4 mL of acetate buffer (pH 3) and 0.3 mL of H 2 O 2 (0.2M) and 0.3mL TMB (2.4mM), incubate at room temperature for 10 minutes, and monitor the change in absorbance of the reaction system at 650nm. Measure once every 2 days for a total of 30 days. Measure 3 times each time and take the average. The results are shown in Figure 4 .

[0070] like Figure 4 As shown, it was found that MnO 2 The catalytic effect of @ZIF-67@MAA was always stable above 94%, indicating its excellent storage stability.

[0071] Example 7

[0072] The present invention provides a method for 2 The selectivity of the tetracycline colorimetric detection method of @ZIF-67@MAA nanocomposite is as follows:

[0073] 2 mg MnO 2 @ZIF-67@MAA was mixed with 2.1 mL acetate buffer (pH = 3), and 0.3 mL TC or other interfering substances (500 μM) were added. TC and each interfering substance were added separately. In addition, there was a blank group (i.e., MnO 2 @ZIF-67@MAA+H 2 O 2 +TMB). Other interfering substances include other antibiotics (chloramphenicol CLP, penicillin PCN and azithromycin AZI), pesticides (acetamiprid and thiamethoxam), metal cations (Na + , K + , Ca 2+ and Mg 2+ ) and amino acids (lysine Lys, valine Val, alanine Ala, leucine Leu, serine Ser and phenylalanine Phe) were shaken at room temperature for 90 min and 0.3 mL of H 2 O 2 (0.2M) and 0.3mL TMB (2.4mM), incubate at room temperature for 10min, and monitor the absorbance change of the reaction system at 650nm. Figure 5 shown. Figure 5In the table, 1 corresponds to blank, 2 corresponds to tetracycline, 3 corresponds to chloramphenicol, 4 corresponds to penicillin, 5 corresponds to azithromycin, 6 corresponds to acetamiprid, 7 corresponds to thiamethoxam, 8 corresponds to sodium ion, 9 corresponds to potassium ion, 10 corresponds to calcium ion, 11 corresponds to magnesium ion, 12 corresponds to lysine, 13 corresponds to valine, 14 corresponds to alanine, 15 corresponds to leucine, 16 corresponds to serine, and 17 corresponds to phenylalanine.

[0074] In addition, in order to be close to the actual detection environment, CLP, PCN and AZI were mixed as the control group, and TC, CLP, PCN and AZI were used as the test group. The concentration of each substance was still 500 μM. The absorbance changes of the two reaction systems at 650 nm were monitored. The results are as follows: Figure 5 As shown in the illustration. Figure 5 In the illustration, 1 corresponds to the blank group, 2 corresponds to the test group, and 3 corresponds to the control group.

[0075] from Figure 5 It can be seen that the absorbance values ​​of the catalytic system with added interfering substances are significantly lower than those of the catalytic system containing TC, indicating that these substances have little effect on the catalytic system and will hardly affect the detection of TC. 2 The sensing platform of @ZIF-67@MAA nanomaterials exhibited acceptable selectivity for TC.

[0076] Example 8

[0077] The present invention provides a method for 2 The recovery rate of tetracycline colorimetric detection method of @ZIF-67@MAA nanocomposite materials was analyzed by the following steps:

[0078] The actual sample to which the TC standard solution was added was added with 2 mg of MnO 2 @ZIF-67@MAA was mixed with 2.1 mL acetate buffer (pH 3) and reacted at room temperature for 90 min, after which 0.3 mL H 2 O 2 (0.2M) and 0.3mL TMB (2.4mM), the mixed system reacted at room temperature for 10min and the absorbance value at 650nm was recorded. According to the measured ΔA and the corresponding colorimetric detection method working curve, the concentration value measured by this method was calculated, and the recovery rate of this method was obtained according to the ratio percentage between the measured concentration value and the actual sample concentration A. The results are shown in Table 1.

[0079] Table 1 TC content and recovery rate in medical wastewater and fresh milk samples (n=3)

[0080]

[0081] As can be seen from the above table, the MnO-based 2 The recoveries of tetracycline colorimetric detection of @ZIF-67@MAA nanocomposites were 95.59-111.89% (medical wastewater), 97.90-115.18% (fresh milk), and the relative standard deviations (RSDs) were 0.30-9.41% (medical wastewater), 1.14-14.15% (fresh milk).

[0082] The invention discloses a novel nano composite material MnO 2 @ZIF-67@MAA, a new type of nanocomposite material MnO 2 @ZIF-67@MAA is a ZIF-67 modified MnO 2 Nanosheets were used as support carriers and catalysts, MAA was used as functional monomer, EGDMA was used as crosslinker, and MAA was synthesized and encapsulated in MnO 2 @ZIF-67 forms a polymer layer on the surface, and finally obtains the composite material MnO 2 @ZIF-67@MAA.

[0083] The composite material MnO 2 When @ZIF-67@MAA detects TC, when the solution contains TC, TC is replaced by MnO 2 @ZIF-67@MAA recognition enables the material to catalyze H 2 O 2 The ability to oxidize TMB is enhanced, the intensity of the blue color produced is promoted, and by detecting the increase in the absorbance value, the visual detection of TC can be achieved.

[0084] New material MnO for colorimetric detection of tetracycline disclosed in the present invention 2 @ZIF-67@MAA, the new material contains MnO 2 The large specific surface area, rich active groups and excellent catalytic performance of ZIF-67 are combined with the high surface activity, chemical stability and thermal stability of ZIF-67, and the performance is excellent, and it has a wide range of application prospects in the field of analysis. The new material provided by the present invention has great application prospects as a colorimetric sensor, has good stability, can be prepared in advance and stored for a long time.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A new material for colorimetric detection of tetracycline, characterized in that: The new material is a nanocomposite material MnO2@ZIF-67@MAA formed by methacrylic acid wrapping MnO2@ZIF-67.

2. The method for preparing the new material for tetracycline colorimetric detection according to claim 1, characterized in that: The steps include: S1. Preparation of MnO2 nanosheets: tetramethylammonium hydroxide aqueous solution, H2O2 solution and manganese chloride aqueous solution are mixed, and after magnetic stirring, the precipitate is washed several times with water and methanol, and then dried to obtain MnO2 nanosheets; S2. Preparation of MnO2@ZIF-67: Mix a methanol solution of cobalt nitrate with MnO2 nanosheets and stir them magnetically; then add a methanol solution of 2-methylimidazole and stir them magnetically; after standing, discard the supernatant, centrifuge, wash the precipitate with methanol several times, and then dry it to obtain MnO2@ZIF-67; S3. Preparation of MnO2@ZIF-67@MAA composite material: methacrylic acid and MnO2@ZIF-67 are added to ethylene glycol dimethacrylate, and after mixing, azobisisobutyronitrile is added to react and polymerize under N2 atmosphere; after the reaction is completed, the obtained solid is washed with methanol until neutral, and then dried to obtain the composite material MnO2@ZIF-67@MAA.

3. The composite material MnO2@ZIF-67@MAA according to claim 1 or the composite material MnO2@ZIF-67@MAA prepared by the method according to claim 2 is used in the colorimetric detection of tetracycline.

4. The use according to claim 3, characterized in that: The composite material MnO2@ZIF-67@MAA was used to perform colorimetric detection of tetracycline. The specific detection method is as follows: (1) Preparation of tetracycline standard solution: Weigh tetracycline powder and dissolve it in ultrapure water, and prepare tetracycline standard solutions of different concentrations by dilution; (2) Preparation of incubation system: MnO2@ZIF-67@MAA was mixed with acetate buffer, and then different concentrations of tetracycline standard solution were added; (3) preparing a reaction system: adding a H2O2 solution and a chromogenic substrate 3,3',5,5'-tetramethylbenzidine solution to the mixed system obtained in step (2) to carry out an incubation reaction; (4) Detection: measuring the ultraviolet absorbance A of the reaction system obtained in step (3) at a wavelength of 650 nm; measuring the absorbance A0 of the reaction system at a wavelength of 650 nm when the target substance tetracycline is not present; then using the concentration of tetracycline as the abscissa and the absorbance difference ΔA between A and A0 as the ordinate to obtain a linear relationship between the tetracycline concentration and the absorbance difference ΔA; (5) MnO2@ZIF-67@MAA is mixed with acetate buffer, and then the sample to be tested is added; after the reaction, H2O2 solution and chromogenic substrate 3,3',5,5'-tetramethylbenzidine solution are added to incubate the reaction; (6) detecting the ultraviolet absorbance of the reaction system in step (5) at a wavelength of 650 nm, and calculating the difference between the ultraviolet absorbance and A0; (7) Based on the difference between the ultraviolet absorbance obtained in step (6) and A0, combined with the linear relationship obtained in step (4), the concentration of tetracycline in the sample to be tested is calculated.

5. The use according to claim 4, characterized in that: The tetracycline standard solutions of different concentrations in step (1) refer to tetracycline concentrations of 1, 2, 5, 10, 50, 100, and 200 μM, respectively.

6. The use according to claim 4, characterized in that: The concentration of MnO2@ZIF-67@MAA in step (2) is 0.67 mg mL -1 ; After adding tetracycline, react at room temperature for 90 minutes.

7. The use according to claim 4, characterized in that: In step (3), the concentration of the H2O2 solution is 0.02 M, the concentration of the 3,3',5,5'-tetramethylbenzidine solution is 0.24 mM, and the incubation reaction is carried out at room temperature for 10 min.

8. The use according to claim 4, characterized in that: Determining the absorbance A0 of the reaction system at a wavelength of 650 nm when the target tetracycline is not present in step (4) means that no tetracycline standard solution is added in step (2), and then the ultraviolet absorbance of the system is measured at a wavelength of 650 nm according to the reaction system obtained in steps (2) and (3), and is recorded as A0.

9. The use according to claim 8, characterized in that: In step (4), the ultraviolet absorbance of the system is measured at a wavelength of 650 nm, specifically: the sample is placed in a UV-visible spectrophotometer and a full wavelength scan of 200 to 800 nm is performed to determine the absorbance value at 650 nm.

10. The use according to claim 4, characterized in that: In step (5), the sample to be tested is medical waste water or milk.

Citation Information

Cited By

  • Composite material for tetracycline multi-mode detection as well as preparation method and application of composite material

    CN121248969A